2020
DOI: 10.3390/w12092552
|View full text |Cite
|
Sign up to set email alerts
|

Submarine Groundwater Discharge in a Coastal Bay: Evidence from Radon Investigations

Abstract: Jiaozhou Bay, an urbanized coastal bay located in the southern part of Shandong Peninsula, China, has been deeply affected by anthropogenic activities. Here, the naturally occurring 222Rn isotope was used as a tracer to assess the submarine groundwater discharge (SGD) in this bay. The time series of 222Rn concentrations in nearshore seawater were monitored continuously over several tidal cycles at two fixed sites (Tuandao (TD) and Hongdao (HD)) during the dry season in spring and the wet season in autumn of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 64 publications
2
4
0
Order By: Relevance
“…The long-time series measurements revealed that the variation of radon activities in seawater (~2.5 m water depth) is inversely correlated with the local tides, with radon peaks generally at low tide (Figure 5). The radon activities at 31.0 ± 11.4 Bq/m 3 during a tidal cycle near the same place of the bay were previously documented by Luo et al (2020), which match well with our results. We measured the 226 Ra activities (6.8 ± 0.6 Bq/ m 3 ) of three seawater samples at different tidal times including high and low peaks, indicating that the radon contributed from the ingrowth of 226 Ra were limited.…”
Section: High Temporal Resolution 222 Rn Observationssupporting
confidence: 93%
See 3 more Smart Citations
“…The long-time series measurements revealed that the variation of radon activities in seawater (~2.5 m water depth) is inversely correlated with the local tides, with radon peaks generally at low tide (Figure 5). The radon activities at 31.0 ± 11.4 Bq/m 3 during a tidal cycle near the same place of the bay were previously documented by Luo et al (2020), which match well with our results. We measured the 226 Ra activities (6.8 ± 0.6 Bq/ m 3 ) of three seawater samples at different tidal times including high and low peaks, indicating that the radon contributed from the ingrowth of 226 Ra were limited.…”
Section: High Temporal Resolution 222 Rn Observationssupporting
confidence: 93%
“…The SGD fluxes in this bay were previously summarized in a range of 12.3-26.9 cm/d by using the radon mass balance models (Luo et al, 2020). Our results were basically in the scope of former documents.…”
Section: Sgd Assessments Based On High Resolution Rn Observationssupporting
confidence: 66%
See 2 more Smart Citations
“…A number of contributions to this Special Issue add specifically to the growing body of literature on submarine groundwater discharge. Luo et al [1] show, based on radon time-series measurements, that submarine groundwater discharge rates to the Jiaozhou Bay (China) are 8-14 times higher than those of the local rivers. By combining radium isotopes, radon, and stable isotopes of nitrate, Knapp et al [2] reveal the importance of submarine groundwater discharge for the primary productivity of coastal waters off Saipan (Northern Mariana Island, US).…”
mentioning
confidence: 99%